Syntheses and Molecular Structures of [(thf)4Li] [(thf)LiM(C4H8)3] (M = Zr, Hf) and Their Solution Behavior. Issue 4 (13th February 2020) - Fischer, Reinald; Schmidt, Heiner; Younis, Fadi M.; Görls, Helmar; Suxdorf, Regina; Westerhausen, Matthias
Abstract : The reaction of MCl4 (thf)2 (M = Zr, Hf) with 1, 4‐dilitiobutane in diethyl ether at –25 °C or at 0 °C with a molar ratio of 1 : 3 yields the homoleptic "ate" complexes [(thf)4 Li] [(thf)LiM(C4 H8 )3 ] 1 ‐Zr (M = Zr) and 1 ‐Hf (M = Hf). The crystalline compounds form ion lattices with solvent‐separated [(thf)4 Li] + cations and [(thf)LiM(C4 H8 )3 ] – anions. The NMR spectra at –20 °C show magnetic equivalence of the M–CH2 and of the β‐CH2 groups of the butane‐1, 4‐diide ligands on the NMR time scale. Analogous reactions of MCl4 (thf)2 with 1, 4‐dilithiobutane with a molar ratio of 1 : 2 proceed unclear. However, single crystals of [Li(thf)4 ] [HfCl5 (thf)] (2 ) can be isolated with the hafnium atom in a distorted octahedral coordination sphere of five chloro and one thf ligand. NMR spectra allow to elucidate the time‐dependent degradation of 1‐Hf and 1‐Zr in THF and toluene at 25 °C via THF cleavage. Addition of tmeda to a solution of 1‐Zr allows the isolation of intermediately formed [(tmeda)Li2 Zr( n Bu)2 (C4 H8 )2 ] (3 ). Abstract :